Effects of island area and distances among islands on their β-diversity of plant species in One-thousand Island Lake region - ZHU Li; LU Jian-bo; YU Lin (浙江大学学报. 农业与生命科学版, 2010)
There are more than one thousand islands in One-thousand Island Lake region. To study plant species β diversity, 10 typical small islands in the centre of lake were selected. Plant species were investigated on each island, and β diversity among islands were calculated. Then relationships between distances (among islands)and corresponding value of β diversity were analyzed. Results showed that: 1)distance had a remarkable effect on the distribution of species. The value of β diversity was lower when the distance among islands was closer, indicating high species similarity; 2)area effects were found by analyzing β diversity values on larger islands. For the larger islands, their β diversity values increased along with the area decreasing of corresponding islands. β diversity values of plant species had no fixed rule when the larger islands were mated with smaller islands. The study of β diversity of plant communities is benefit to the conservation of plant species diversity, and to guide the construction of biological diversity protected areas.